Overview of Risk Factors for the Incidence of Pediculosis Capitis in Children - Marliana Nurprilinda; Eva Silvia F Sitanggang; Mulyadi Djojosaputro; Dartri Cahyawari (Indonesian Journal of Global Health Research, 2025)
Pediculosis capitis (head lice) is a global health issue, particularly among school-aged children, caused by Pediculus humanus capitis. This condition can be transmitted both directly or indirectly via fomites. Symptoms commonly associated with Pediculosis capitis include itching of the scalp, sleep disturbances, and discomfort. Several factors generally influence the prevalence, including age, gender, frequency of hair washing, hair type, level of knowledge, personal hygiene, living conditions, and shared use of bedding or pillows. Research purposes to identify the risk factors associated with Pediculosis capitis among students at SDN Cawang 04 and SDN Cawang 12 in East Jakarta. This research is an analytical study with a cross-sectional approach. The research method employed is quantitative, utilizing questionnaires as research instruments and visual inspection to diagnose infestation, which is confirmed if eggs, nymphs, or adult lice are found in the hair. The sample was selected through random sampling from students in grades 3,4, and 5, with a total of 180 respondents determined using the Slovin formula. Data collection in this study used primary data collected through head lice or nit examinations and questionnaires. The research instruments used were a questionnaire regarding sociodemographic characteristics and questions to determine the number and risk factors for head lice. Data were analyzed using univariate analysis in SPSS. The results show that out of 180 respondents, 100 people (55.6%) were positive for Pediculosis capitis, with a higher infestation rate among female students (76, 42.2%) compared to male students (24, 13.3%). Based on respondent characteristics, the most common age was 9 years old, namely 39 people (21.6%), and grade IV, 37 people (20.5%). Dominant risk factors include age, gender, having long hair, a family size of more than four members, and parents' highest education level being high school. This study indicates that the incidence of Pediculosis capitis remains relatively high.